Layer-specific proteomic analysis of human hearts in patients with sudden cardiac death - Yu Kakimoto; Xueting Guan; Atsushi Ueda; Yayoi Kimura; Tomoko Akiyama; Masayuki Tanaka; Haruka Ikeda; Kazuho Maeda; Shotaro Isozaki (PLoS ONE, 2025)
Background Recent studies have shown that decreased longitudinal strain in speckle-tracking echography can predict sudden cardiac death (SCD) in patients with cardiac hypertrophy (CH). Histologically, the heart wall consists of the inner longitudinal, middle circular, and outer longitudinal layers. Thus, layer-specific proteomic changes may contribute to SCD risk. Methods The three layers in human cardiac tissues were obtained during autopsies of SCD, compensated CH, and control cases (18 cases aged > 40 years, 54 samples in total). SCD cases consisted of patients with ischemic or hypertensive heart failure, whereas CH and control cases were accidental deaths. After histological analysis, cardiomyocytes were collected separately from the three layers of the left ventricular wall using laser microdissection. The extracted proteins were analyzed using liquid chromatography–tandem mass spectrometry, followed by label-free quantification. Results and discussion Histologically, cardiomyocytes were enlarged in all layers of SCD and CH cases without significant progression of myocardial fibrosis. The proteomic profiles of SCD and CH cases were distinguishable from those of control cases, especially in the inner layer. The levels of mitochondrial and calcium-handling proteins were significantly decreased in SCD hearts. Arrhythmogenic changes, including decreased PKP2 and RYR2 levels, developed in a stepwise manner from control through CH to SCD, most prominently in the inner layer. Immunohistochemical analysis showed reduced levels of PKP2 in intercalated disks and RYR2 in sarcomeres. Because proteomic alterations precede the progression of myocardial fibrosis, their detection may enhance the accuracy of postmortem diagnosis of SCD in middle-aged and older asymptomatic individuals with CH.